2015
DOI: 10.5301/jva.5000374
|View full text |Cite
|
Sign up to set email alerts
|

Revision Techniques for Failed PD Catheters: Outcome in a University Hospital

Abstract: The salvage of the catheter by means of a laparoscopic procedure or correction of a hernia is worthwhile and can save up to 81% of the catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…However, because of the small numbers we could not observe a trend in this difference (3/6 of patients, 50% in the open surgery group versus 11/16 of patients, 69% in the laparoscopic group; p = 0.62). As previously described by our group, when revision techniques were used, we could increase the overall rate of adequate functioning catheters up to 90% in both groups (15).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…However, because of the small numbers we could not observe a trend in this difference (3/6 of patients, 50% in the open surgery group versus 11/16 of patients, 69% in the laparoscopic group; p = 0.62). As previously described by our group, when revision techniques were used, we could increase the overall rate of adequate functioning catheters up to 90% in both groups (15).…”
Section: Resultsmentioning
confidence: 53%
“…This technique can be time-consuming and was done in an interventional radiologic suite. If this failed, surgical techniques were used to improve the position and thus enhance function of the catheter, such as omentectomy and fixation of the catheter, as has earlier been described by our group (15).…”
Section: Methodsmentioning
confidence: 99%
“…Laparoscopic insertion and omentectomy are more often recommended as a salvage procedure for blocked PD catheters. [ 10 13 14 15 ] A purported advantage of laparoscopic PDCI (in addition to facilitating omentectomy through small incisions) is that it also facilitates lysis of intraperitoneal adhesions. Patients who have had previous abdominal surgery or PD peritonitis are more prone to adhesion formation.…”
Section: Discussionmentioning
confidence: 99%
“…After scrutinizing literature, we concluded that omental removal might improve our outcome, since omental wrapping causes most catheter failures. Also in our previous publication, we proved removal of the omentum to be successful; however, this is a challenging procedure [ 3 ]. Fixation of the omentum has been shown to be a safe and feasible alternative to prevent omental wrapping [ 9 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative complications can be obstruction of flow through the catheter, catheter migration, fluid leaks, erosion of catheter into viscera, and sclerosing or bacterial peritonitis [ 1 ]. Various causes for catheter obstruction are identified such as omental wrapping, adhesions, and catheter migration [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%